Dental bio-aerosol: a potential occupational hazard in dental practice - Arief Ichwan, Solachuddin Jauhari (2015)
Dental health care workers (DHCWs) are regularly exposed to a wide variety of air pollutants including dental bio-aerosols during routine dental work. Dental bio- aerosols are defined as airborne particles of liquid that contain living organisms or have been released from living organisms, which are generated during many dental procedures. Devices such as dental handpieces, ultrasonic scalers, air polishers, air- water syringes, and air abrasion units produce extensive aerosols that are routinely contaminated with bacteria, viruses, and blood. The potential for airborne spread of disease in a dental office has been considered for many years. Dental bio-aerosol has the potential for the airborne spread of disease since air contained within the office is breathed by DHCWs. Aerosolized microorganism emerges from a patient’s mouth during dental treatment procedures may remain suspended in the air for long periods of time and inhaled into the lungs of a susceptible person. Microorganisms in the bio-aerosols have also been associated with bacterial diseases such as tuberculosis, staphylococcal infection, conjunctivitis, viral infections and other skin infections. Eliminating the risk of exposure to dental bio-aerosol remains challenging. Dental personnel are urged to make the control of aerosols a standard part of their infection control procedures. To date, various infection control reports and procedures have been published to inform and educate dental health care personnel about the importance of practicing adequate infection control. This brief review highlights the reasons and the potential risks that can be encountered with dental bio-aerosol. Various protective measures against these risk factors are also discussed.